TRP Channels as Molecular Targets to Relieve Endocrine-Related Diseases - Liu, Yusheng; Lyu, Yihan; Wang, Hongmei (Frontiers in Molecular Biosciences, 2022)
TRP channels are polymodal channels capable of sensing environmental stimuli, which are widely expressed on the plasma membrane of cells and play an essential role in the physiological or pathological processes of cells as sensors. TRPs often form functional homo- or heterotetramers that act as cation channels to flow Na+ and Ca2+, change membrane potential and [Ca2+]i, and change protein expression levels, channel attributes, and regulatory factors. Under normal circumstances, various TRP channels respond to intracellular and extracellular stimuli such as temperature, pH, osmotic pressure, chemicals, cytokines, and cell damage and depletion of Ca2+ reserves. As cation transport channels and physical and chemical stimulation receptors, TRPs play an important role in regulating secretion, interfering with cell proliferation, and affecting neural activity in these glands and their adenocarcinoma cells. Many studies have proved that TRPs are widely distributed in the pancreas, adrenal gland, and other glands. This article reviews the specific regulatory mechanisms of various TRP channels in some common glands (pancreas, salivary gland, lacrimal gland, adrenal gland, mammary gland, gallbladder, sweat gland).